(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
As a critical component of any healthy civilization, information is essential to the advancementof all humanity. People with disabilities are acquiring informational requirements at the same rate as thegeneral population. People with disabilities constitute a substantial portion of our population, and it is ourresponsibility as members of society to ensure they have equal access to all possibilities. Access toinformation for all users, including those with physical restrictions, has vastly increased in recent yearsdue to technology improvements. Today, conveying data frequently requires electronic access,networked resources, and other forms of information and communication technology (ICT). Due to therapid development of ICT, information is now accessible within seconds. The gap is closed by assistivetechnology, which facilitate access to a broad variety of resources that would otherwise be unavailableto people with impairments. This article investigates the Awareness and Use of Assistive Technologiesfor Information Support by People with Disabilities.